Etiology of acute gastroenteritis among children less than 5 years of age in Bucaramanga, Colombia: A case-control study - Farfán-García, Ana E.; Imdad, Aamer; Zhang, Chengxian; Arias-Guerrero, Mónica Y.; Sánchez-Álvarez, Nayibe T.; Iqbal, Junaid; Hernández-Gamboa, Adriana E.; Slaughter, James C.; Gómez-Duarte, Oscar G. (PLOS Neglected Tropical Diseases, 2020)
Background Acute gastroenteritis (AGE) is a major cause of morbidity and mortality in children aged less than 5 years in low- and middle-income countries where limited access to potable water, poor sanitation, deficient hygiene, and food product contamination are prevalent. Research on the changing etiology of AGE and associated risk factors in Latin America, including Colombia, is essential to understand the epidemiology of these infections. The primary objectives of this study were to describe etiology of moderate to severe AGE in children less than 5 years of age from Bucaramanga, Colombia, a middle-income country in Latin American, and to identify the presence of emerging E. coli pathotypes. Methodology/Principal findings This was a prospective, matched for age, case-control study to assess the etiology of moderate to severe AGE in children less than 5 years of age in Bucaramanga, Colombia, South America. We tested for 24 pathogens using locally available diagnostic testing, including stool culture, polymerase chain reaction, microscopy and enzyme-linked immunoassay. Adjusted attributable fractions were calculated to assess the association between AGE and each pathogen in this study population. The study included 861 participants, 431 cases and 430 controls. Enteric pathogens were detected in 71% of cases and in 54% of controls (p = <0.001). Co-infection was identified in 28% of cases and in 14% of controls (p = <0.001). The adjusted attributable fraction showed that Norovirus GII explained 14% (95% CI: 10–18%) of AGE, followed by rotavirus 9.3% (6.4–12%), adenovirus 3% (1–4%), astrovirus 2.9% (0.6–5%), enterotoxigenic Escherichia coli (ETEC) 2.4% (0.4–4%), Cryptosporidium sp. 2% (0.5–4%), Campylobacter sp. 2% (0.2–4%), and Salmonella sp.1.9% (0.3 to 3.5%). Except for Cryptosporidium, all parasite infections were not associated with AGE. Three emergent diarrheagenic E. coli pathotypes were identified in cases (0.7%), including an enteroaggregative/enterotoxigenic E.coli (EAEC/ETEC), an enteroaggregative/enteropathogenic E.coli (EAEC/EPEC), and an emergent enteroinvasive E. coli with a rare O96:H19. No deaths were reported among cases or controls. Conclusions/Significance Norovirus and rotavirus explained the major proportion of moderate to severe AGE in this study. Higher proportion of infection in cases, in the form of single infections or co-infections, showed association with AGE. Three novel E. coli pathotypes were identified among cases in this geographic region.